The Development of a Survey Instrument to Assess Aboriginal and Torres Strait Islander Students’ Resilience and Risk for Self-Harm - McCalman, Janya; Bainbridge, Roxanne Gwendalyn; Redman-MacLaren, Michelle; Russo, Sandra; Rutherford, Katrina; Tsey, Komla; Ungar, Michael; Wenitong, Mark; Hunter, Ernest (Frontiers in Education, 2017)
8 Background: Australian policies for Aboriginal and Torres Strait Islander wellbeing outline 9 the importance of local community-based interventions; for adolescents, school-based 10 programs are considered beneficial. However, there is a lack of localised data to determine 11 levels of resilience and risk, and thus whether programs are effective. This paper describes the 12 challenges and opportunities in collaboratively designing and piloting a localised survey 13 instrument to measure Indigenous students’ resilience and upstream risk factors for self-harm; 14 and the resultant instrument. 15 Methods: A participatory action research approach was used to engage education staff, health 16 care providers, students and researchers to design and pilot the survey instrument. A six-phased 17 process facilitated survey development: 1) defining the logic and exploring the evidence; 2) 18 understanding and tailoring for context; 3) testing for feasibility and relevance; 4) testing for 19 appropriateness and comprehension; 5) facilitating survey administration; and 6) refining the 20 instrument. Processes in each phase were recorded and transcribed with thematic analysis used 21 to identify key challenges and opportunities arising during development. 22 Results: Four key challenges and opportunities were identified: 1) the relevance of 23 international survey instruments for Indigenous Australian students; 2) accounting for distinct 24 environments; 3) the balance between assessing risk and protective factors; and 4) tailoring 25 for literacy levels and school engagement. The final Student Survey instrument comprised 26 four demographic, 44 resilience, nine risk and 35 service use and satisfaction questions. The T4S will 27 be administered routinely on annual student intake. 28 29 Discussion and conclusion: The six-phased participatory processes resulted in a tailored 30 instrument that could identify the critical resilience and upstream risk factors facing a cohort 31 of Indigenous students who attend boarding schools for secondary education. Challenges 32 were resolved collaboratively and the pilot results were directly translated to education 33 practice and its integration with health services. Our results suggest that both the phased 34 process of developing the T4S, and the instrument itself can be adapted for other Indigenous 35 adolescent wellbeing and/or self-harm prevention programs.